Philosophy of human rights : concept and justification theories - Hapla, Martin, 1988-; Dibble, Graeme; Masarykova univerzita; Munipress (nakladatelství) (Brno : Masaryk University Press, 2025)
In practical terms, the concept of human rights is a very successful one. They are at the centre of discussions among lawyers, politicians and journalists. In the realm of theory, however, they remain a source of doubt. In particular, the question arises as to what grounds justify them. This book seeks to answer this question by linking them to utilitarian ethics. As controversial as this connection is sometimes perceived to be, it was already sought by John Stuart Mill and is still the subject of lively debate today. The book sets these within the broader framework of human rights theory and the problems associated with it. In doing so, the book not only introduces the reader to utilitarianism itself and the various ways in which it can be applied in this area, but also provides a representative overview and critical analysis of the most debated approaches to justifying human rights today.
Kniha se zabývá filozofií lidských práv a jejich teoretickým zdůvodněním, zejména ve vztahu k utilitarismu. Představuje hlavní přístupy k ospravedlnění lidských práv, analyzuje jejich silné a slabé stránky a zasazuje je do širšího kontextu současných filozofických debat. Současně nabízí úvod do utilitaristické etiky a její aplikace v oblasti lidských práv.
Přeloženo z češtiny
Obsahuje bibliografické odkazy
Keywords: utilitarismus; lidská práva; přirozené právo; monografie; utilitarianism; human rights; natural law; monographs